2015
DOI: 10.1177/1060028015581009
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Frequency and Nature of Medication-Related Problems in the Women’s Health Unit of an Australian Tertiary Teaching Hospital

Abstract: The widespread nature of identified MRPs in this setting suggests that various approaches to minimizing these problems and mitigating the associated burden on the health care system are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 27 publications
4
45
3
Order By: Relevance
“…In addition, studies in non-pregnant patients have shown the effectiveness of pharmacists' counselling on medication adherence, persistence, clinical management and therapeutic outcomes [16][17][18][19][20][21][22]. This is important since two recent studies have shown medication-related problems (MRP) frequently occur among pregnant women [23,24]. These MRP were largely resolved by pharmacists correcting misperceptions, providing information, and empowering the women to make safe decisions about medication use [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies in non-pregnant patients have shown the effectiveness of pharmacists' counselling on medication adherence, persistence, clinical management and therapeutic outcomes [16][17][18][19][20][21][22]. This is important since two recent studies have shown medication-related problems (MRP) frequently occur among pregnant women [23,24]. These MRP were largely resolved by pharmacists correcting misperceptions, providing information, and empowering the women to make safe decisions about medication use [23].…”
Section: Introductionmentioning
confidence: 99%
“…MRPs were classi ed into eight categories: need for additional drug therapy, unnecessary drug therapy, dose too low, dose too high, ineffective drug, adverse drug reactions, noncompliance [1], and other, subdivided into need for additional laboratory test and/or incomplete drug order (Additional le 1) [3].…”
Section: Mrp Identi Cation and Assessmentmentioning
confidence: 99%
“…A panel of experts comprised of senior clinical pharmacists and experienced obstetricians/gynaecologists identi ed MRPs and classi ed them into categories as recommended by Cipolle et al [22]. The panel of experts further re ned the MRP identi cation and classi cation method for the study setting in accordance with Ethiopian standard treatment guidelines and literature reviews (Additional le 1) [3,[23][24][25][26].…”
Section: Mrp Identi Cation and Assessmentmentioning
confidence: 99%
See 2 more Smart Citations